2022
DOI: 10.1080/03098265.2022.2155935
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining geographical competences through online cartography of familiar and unfamiliar urban heritage: lessons from student workshops

Abstract: In times of the COVID-19 pandemic, teachers on all levels have had to adapt to an online or hybrid teaching environment. People in geography, a discipline that traditionally values field trips to connect theory to practice, have had to find online alternatives for educational activities that normally would have taken place in the field.This has led to several innovative practices, which, however, have only to a limited degree been purposively tested for efficacy because of the ad-hoc, enforced nature of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…This article presents the design of workshops on web GIS story maps applied to the identification of urban heritage by teachers in training. Martínez-Hernández et al (2022) already demonstrated the workshops' learning effectiveness. In this paper we focus on design elements to reflect on the conditions that allow making most of online web-based GIS workshops, so that this effectiveness can be achieved.…”
Section: Literature Reviewmentioning
confidence: 86%
See 4 more Smart Citations
“…This article presents the design of workshops on web GIS story maps applied to the identification of urban heritage by teachers in training. Martínez-Hernández et al (2022) already demonstrated the workshops' learning effectiveness. In this paper we focus on design elements to reflect on the conditions that allow making most of online web-based GIS workshops, so that this effectiveness can be achieved.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Moreira et al (2023), in line with the transposition theory and the digital teaching environment models, summarized these good practices into six teaching competencies or didactic transference abilities (DTA), from a systematic literature review: Finally, the methodological fourth step (didactic basis for the evaluation of the workshop, that is, the third research objective) also took place in a descriptive qualitative way. The workshop's assignment statements partially provided by Martínez-Hernández et al (2022), as evidence items of the acquisition level of the workshop learning outcomes, were connected to the three key concepts of the didactic framework of the workshop pedagogical goal (GRS, HIC and DTA), in a detailed description.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations